1998
DOI: 10.1023/a:1022292801256
|View full text |Cite
|
Sign up to set email alerts
|

Computational Observation of an Ion Permeation Through a Channel Protein

Abstract: The ion permeation process, driven by a membrane potential through an outer membrane protein, OmpF porin of Escherichia coli, was simulated by molecular dynamics. A Na+ ion, initially placed in the solvent region at the outer side of the porin channel, moved along the electric field passing through the porin channel in a 1.3 nsec simulation; the permeation rate was consistent with the experimentally estimated channel activity (10(8)-10(9)/sec). It this simulation, it was indicated that the ion permeation throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 13 publications
4
62
0
Order By: Relevance
“…Accordingly, its structure displays a large number of basic residues inside the pore and an unusually narrow constriction zone located approximately halfway along the pore axis (25). Recent MD studies showed that even the small chloride ions experience intimate interactions with charged amino acids arranged as a "basic ladder" and located in the channel constriction (26), a situation that is less obvious but also present in porins exhibiting a larger pore cross-section such as OmpF from Escherichia coli (27,28). The affinity of D. acidovorans toward organic acids as carbon source, together with the strong anion selectivity and the small channel diameter of Omp32, suggests that a certain level of substrate specificity may also be present in a porin that would be attributed as unspecific by its structure according to the current classification (3).…”
mentioning
confidence: 99%
“…Accordingly, its structure displays a large number of basic residues inside the pore and an unusually narrow constriction zone located approximately halfway along the pore axis (25). Recent MD studies showed that even the small chloride ions experience intimate interactions with charged amino acids arranged as a "basic ladder" and located in the channel constriction (26), a situation that is less obvious but also present in porins exhibiting a larger pore cross-section such as OmpF from Escherichia coli (27,28). The affinity of D. acidovorans toward organic acids as carbon source, together with the strong anion selectivity and the small channel diameter of Omp32, suggests that a certain level of substrate specificity may also be present in a porin that would be attributed as unspecific by its structure according to the current classification (3).…”
mentioning
confidence: 99%
“…Second, the variation in the concentration of mobile ions inside the channel due to adsorption processes as suggested by a number of different approaches. Thus, fluorescence experiments [21], MD simulations [22], free-energy calculations [13], and site-directed mutagenesis experiments [23] pointed to the existence of a binding site for monovalent cations located around the central constriction of the OmpF channel [13,14,22]. X-ray structures in MgCl 2 showed a binding site in the selectivity filter [24] as confirmed by selectivity experiments involving selected mutants in salts of multivalent cations [25].…”
Section: Resultsmentioning
confidence: 86%
“…Realistic simulations of porins have been performed with explicit ions, solvent molecules 105 and also phospholipid bilayer membrane. 106 To explore the mechanism of ion conduction, Suenaga et al simulated OmpF in the presence of an applied transmembrane potential.…”
Section: Porinsmentioning
confidence: 99%
“…106 To explore the mechanism of ion conduction, Suenaga et al simulated OmpF in the presence of an applied transmembrane potential. 105 The translocation of a single Na + through the channel was observed in 1.3 ns under the influence of a potential of 500 mV. Tieleman and Berendsen 106 generated a 1 ns MD simulation of an atomic model of OmpF trimer embedded into an explicit phospholipid bilayer membrane with a few explicite counterions (those needed to balance the total charge of OmpF).…”
Section: Porinsmentioning
confidence: 99%